Feasibility analysis of rates of PDAM, South Halmahera district, North Maluku based on full cost recovery - Maralus Samosir; Eduward Tony Sitorus; Ringkot P Nainggolan (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2023)
This study aims to conduct an analysis of the feasibility of PDAM tariffs in South Halmahera Regency based on full cost recovery. In 2018, the average water tariff per m3 was IDR 3,046.41, or 53.67% of the essential cost of water per m3 of IDR 5,676.60. Whereas for 2019, the average water tariff per m3 is IDR 3,112.35, or 52.02% of the crucial cost of water per m3 of IDR 5,982.96. In 2018 and 2019, the selling price of water was still below the basic price of water, so the applicable average tariff did not fully cover costs (full cost recovery). This happened because it used the 2006 water tariff. PDAM Halmahera Selatan Regency has never proposed a new tariff policy. It has yet to evaluate its tariff policy every year because it focuses on its social role in serving the community's water supply and expanding service coverage. PDAM has also never received operational assistance subsidies from the South Halmahera Regency Government. Public interest statements This study proposes tariff changes that can cover total costs (full cost recovery) for the Regent of South Halmahera Regency. If the tariff proposal is not approved, the PDAM should seek operational assistance subsidies to cover the full costs from the South Halmahera Regency Government. If the two efforts are unsuccessful, the PDAM must carry out cost efficiencies to reduce the high operating expenses.